TANGGAPAN JARAK PAGAR (Jatropha curcas Linn) TERHADAP JENIS MEDIA TANAM DAN PUPUK KANDANG AYAM (Response Jatropha curcas On Types Of Plant Media And Chicken Fertilizer): Surawijaya, P 1), Saraswati, D 1), Nababan. E.E.P 1) - Administrator Journal (Fakultas Pertanian Universitas Palangka Raya, 2018)
ABSTRACKThis study aims to : (1) to study the interaction between different planting media and the provisionof chicken fertilizer to the vegetative growth of Jatropha curcas, (2) to the effect of differentplanting media on vegetative growth of Jatropha curcas (3) to study the application of chickenfertilizer to vegetative growth of jatropha plant. The results showed that there was an interactionbetween planting media and the provision of chicken fertilizer. The applying of 20 t.ha-1 and peatsoil is the best treatment to enhance the plant height, the number of leaves and the diameter of thejatropha. Planting media hand a significant effect on plant height, leaf number and diameter ofjatropha. Peat soil treatment increased the growth of plant height (58.19 cm), leaf number (31.17strands) and stem diameter (2.06 cm) at age 12 WAP. chickens fertilizer affected plant height,number of leaves, stem diameter and number of branches. The treatment of 20 t.ha-1increased theplant height (62,89 cm), number of leaves (32,33 strands), number of branch (0,89) and stemdiameter (2,20 cm) at age 12 WAP.Keywords: Planting Media, Chicken Fertilizer, Jatropha Curcas.